Hubungan Efikasi Diri Dengan Burnout Pada Perawat Rumah Sakit X: The Relationship Between Self-Efficacy and Burnout Among Nurses at Hospital X - Regina Nadliroh; Ghozali Rusyid Affandi (Academia Open, 2025)
General Background: Burnout among nurses remains a critical issue in hospital settings due to high workload, emotional demands, and organizational pressures that may compromise psychological well-being. Specific Background: Self-efficacy is considered an internal psychological resource that supports coping capacity and professional functioning among healthcare workers. Knowledge Gap: Although prior studies have examined burnout in nursing contexts, empirical evidence regarding the relationship between self-efficacy and burnout within the studied hospital setting remains limited. Aims: This study aims to examine the relationship between self-efficacy and burnout among hospital nurses. Results: The findings indicate a significant negative relationship between self-efficacy and burnout, demonstrating that higher levels of self-efficacy are associated with lower levels of burnout among nurses. Novelty: This study provides empirical confirmation of the association between self-efficacy and burnout within a specific hospital context, reinforcing the role of personal psychological resources in occupational well-being. Implications: The findings highlight the importance of strengthening nurses’ self-efficacy as part of institutional strategies to address burnout and support sustainable healthcare service delivery. Keywords: Self-Efficacy, Burnout, Nurses, Occupational Stress, Hospital Setting Key Findings Highlights: higher personal confidence in task capability corresponds with lower emotional exhaustion levels psychological resources play a central role in workplace strain among healthcare staff empirical data confirm a significant inverse association between the two measured variables